Qualitative research design for software users - Di Gregorio, Silvana; Davidson, Judith (Open University Press, 2008)
This book is an essential guide for anyone using qualitative data analysis software (QDAS), particularly useful for those who want to go beyond a basic introduction to discover how to get the most out of software and how to identify the methodological issues they need to consider